2019
DOI: 10.1007/s12350-018-1325-5
|View full text |Cite
|
Sign up to set email alerts
|

18F-sodium fluoride positron emission tomography assessed microcalcifications in culprit and non-culprit human carotid plaques

Abstract: Background 18 F-NaF positron emission tomography (PET) targets microcalcifications. We compared in vitro microPET assessed 18 F-NaF uptake between culprit and non-culprit human carotid plaques. Furthermore, we compared 18 F-NaF uptake with calcification visualized on microcomputed tomography (microCT). Methods Carotid plaques from stroke patients undergoing surgery were incubated in 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 42 publications
1
41
0
1
Order By: Relevance
“…5 Sodium 18F-fluoride ( 18 F-NaF) PET/CT is a novel imaging technique that can visualize smaller calcifications. [6][7][8][9][10] In the femoral arteries, 18 F-NaF PET can visualize ongoing (medial and intimal) calcification. 11 In the coronaries 18 F-NaF PET is associated with high risk plaque features and plaque rupture.…”
Section: Introductionmentioning
confidence: 99%
“…5 Sodium 18F-fluoride ( 18 F-NaF) PET/CT is a novel imaging technique that can visualize smaller calcifications. [6][7][8][9][10] In the femoral arteries, 18 F-NaF PET can visualize ongoing (medial and intimal) calcification. 11 In the coronaries 18 F-NaF PET is associated with high risk plaque features and plaque rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Carotid plaques of asymptomatic patients would have represented a better comparator to evaluate FNa binding in stable plaques, but are more difficult to collect as indications for carotid endarterectomy in this population are declining. The study of Hop, et al 5 confirms that FNa is binding to ruptured atherosclerotic plaques, but does not allow us rule on the interest of FNa to discriminate between highrisk and stable lesions.…”
Section: Fna Accumulates In Culprit Atherosclerotic Plaquesmentioning
confidence: 93%
“…A possible explanation for this finding is that plaque vulnerability is a systemic process 6 meaning that carotid lesions contralateral to the territory of the ischemic stroke often also present features of complicated plaques. Indeed, Hop et al 5 confirmed that all nonculprit lesions that bound FNa had features of complicated plaques on histology. Carotid plaques of asymptomatic patients would have represented a better comparator to evaluate FNa binding in stable plaques, but are more difficult to collect as indications for carotid endarterectomy in this population are declining.…”
Section: Fna Accumulates In Culprit Atherosclerotic Plaquesmentioning
confidence: 96%
See 2 more Smart Citations